Actual Surveillance of Children with Bronchial Asthma - Elena A. Vishneva; Leyla S. Namazova-Baranova; Anna A. Alekseeva; Gennadii A. Novik; Kamilla E. Efendieva; Julia G. Levina; Elena A. Dobrynina; Liliya R. Selimzyanova (Педиатрическая фармакология)
The article is devoted to the problem of timely diagnosis and current principles of management of children with bronchial asthma. Given the  increase in the prevalence of allergic pathology stated over the past  decades, the issues of differential diagnosis, integrated approach to the  treatment and management of children with allergies are extremely  relevant. Strategies of sequential therapy and monitoring of the  patient’s condition, adherence principles are key links in achieving and  maintaining control over bronchial asthma. The publication presents the  main provisions of national clinical guidelines developed and approved  by the professional association «Union of Pediatricians of Russia».